Prognostic significance of ASXL1, JAK2V617F mutations and JAK2V617F allele burden in Philadelphia-negative myeloproliferative neoplasms - Yonal-Hindilerden, Ipek (J Blood Med, 2015)
BACKGROUND: Despite insights into the genetic basis of Philadelphia-negative myeloproliferative neoplasms (Ph-negative MPNs), a significant proportion of essential thrombocythemia (ET) and primary myelofibrosis (PMF) patients present with no known MPN disease alleles. There were no previous studies investigating the impact of ASXL1 mutations in Ph-negative MPNs in Turkey. In the current study, we investigated the prognostic significance of ASXL1 mutations in Turkish MPN patients. We also aimed to determine the prognostic significance of JAK2V617F allele burden and the relationship of JAK2V617F mutation with ASXL1 mutations in Ph-negative MPNs. METHODS: About 184 patients from a single center diagnosed with Ph-negative MPNs were screened for ASXL1, JAK2V617F mutations, and JAK2V617F allele burden: 107 ET and 77 PMF. RESULTS: A total of 29 ASXL1 mutations were detected in 24.7% of PMF and 8.4% of ET patients. ASXL1-mutated ET patients showed a trend toward an increase in the incidence of cerebrovascular events and higher total leukocyte counts. ASXL1-mutation in PMF was associated with older age and a higher prevalence of bleeding complications. In univariate analysis, overall survival (OS) was significantly reduced in ASXL1-mutated PMF patients. In multivariate analysis, Dynamic International Prognostic Scoring System-plus high-risk category and ASXL1 mutation status were independently associated with shorter survival in PMF. In PMF, mutational status and allele burden of JAK2V617F showed no difference in terms of OS and leukemia-free survival. CONCLUSION: We conclude that ASXL1 mutations are molecular predictors of short OS in PMF.